The Armed Forces of Southeast Asia in 2020 - Loo, Bernard Fook Weng (2016)
A fundamental question that the armed forces of Southeast Asia will have to ask of themselves is what their future shape and structure will be. How the regional armed forces answer this question will be shaped by three considerations.